Book Review: Disaster Risk - Suparji; Wahito Nugroho, Heru Santoso; Sunarto; Astin Nur Hanifah; Prayogi, Agus Sarwo (National Journal of Community Medicine, 2024)
The book "Disaster Risk: A Comprehensive Overview" provides a comprehensive view of disaster risk, covering scientific, social and policy perspectives. The author analyzes the factors that influence vulnerability to disasters as well as effective mitigation strategies. This book discusses definitions, basic concepts, history of disaster risk management, various types of disasters, and the importance of interdisciplinary approaches and collaboration between various parties. This book also reviews international policies and provides recommendations for the integration of disaster risk management in sustainable development planning.